(untitled) (Applied History Journal of Merong Mahawangsa, 2025)
This paper presents a critical analysis of Malaysia’s arts and culture under the National Culture Policy (NCP) and the Islamization policies of the 1980s. While these sought to create a unifying national culture on Malay and Islamic values, these have, in return, sparked a big debate on arts freedom, inclusion, and creative freedom. This study, based on a qualitative study, sought to examine in which ways arts practitioners negotiated, resisted, or made accommodations in these regulations. The paper captures, in addition, a struggle between imposed narratives of culture and arts freedom, adding a contribution toward a wider debate on decolonization and postcolonial identity in Malaysia. Comparative studies of Nigeria and South Africa, and debates on globalization and digital arts, place Malaysia on a different trajectory